Primeiro registro na América Latina do manjericão (Ocimum basilicum L., 1753) (Lamiaceae) como hospedeiro do ácaro Brevipalpus obovatus Donnadieu, 1933 (Tenuipalpidae) - Poderoso, Júlio César Melo (2009)
The tenuipalpid mites represent important pests for several agricultural crops around the world. During prospection in Ocimum basilicum plants in a medicinal plant nursery of Federal University of Sergipe in São Cristovão District, Sergipe State, Brazil, the occurrence of spider mites was observed in 80% of the seedlings that were taken to the laboratory in order to characterize the damage. Seedlings presented leaf reduction and deformation. About 100 mite specimens were collected from the affected plants and used to mount microscopic slides for taxonomic identification. The mites were identified as Brevipalpus obovatus Donnadieu, 1933 (Tenuipalpidae). This is the first report of O. basilicum as a host plant to B. obovatus in Latin America.